Π⋯π interaction directed 2D FeNi-LDH nanosheets from 2D Hofmann-MOFs for the oxygen evolution reaction. Issue 4 (5th January 2022) - Huo, Jia-Min; Wang, Ying; Meng, Jie; Zhao, Xin-Yi; Zhai, Quan-Guo; Jiang, Yu-Cheng; Hu, Man-Cheng; Li, Shu-Ni; Chen, Yu
Abstract : A two-dimensional (2D) MOFs transformation strategy was introduced to synthesize FeNi layered double hydroxides (FeNi LDHs) in NaBH4 solution, which show excellent OER catalytic activity in alkaline media. Abstract : Layered double hydroxides (LDHs) have attracted much attention for the oxygen evolution reaction (OER) in electrochemical water splitting. In this work, we use a two-dimensional (2D) MOF transformation strategy to synthesize FeNi layered double hydroxides (FeNi LDHs). 2D FeNi Hofmann MOFs ([Fe(L)2 Ni(CN)4 ]) with a similar structure but different ligands (L = py, ISOQ) are synthesized as precursors. Accordingly, hydrolysis transformation assisted by NaBH4 leads to the growth of 2D FeNi-LDH nanosheets from 2D Hofmann-MOFs. During hydrolysis, OH − ions preferentially attack the coordination bond of [Fe(L)2 Ni(CN)4 ], which allows FeNi-LDHs to form quickly on the surface of 2D MOFs. This rapid conversion process can effectively avoid the self-accumulation of LDHs. The hydrogen bubbles produced by NaBH4 can also inhibit the self-stacking of LDHs, which expose ample active species for the OER. Meanwhile, the synergistic effect between Fe and Ni contributes to the outstanding OER performance of FeNi-py-LDH, which shows an overpotential of 238 mV at 10 mA cm −2, a Tafel slope of 22 mV dec −1 and an excellent stability for 15 h. This work provides a universal synthesis method for ultra-thin FeNi-LDHs, which avoids the self-stacking of nanosheets and offers new insights into the OER.